2008
DOI: 10.1371/journal.pone.0003787
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Newly Identified Group B Streptococcus Pullulanase Eliciting Antibodies Able to Prevent Alpha-Glucans Degradation

Abstract: Streptococcal pullulanases have been recently proposed as key components of the metabolic machinery involved in bacterial adaptation to host niches. By sequence analysis of the Group B Streptococcus (GBS) genome we found a novel putative surface exposed protein with pullulanase activity. We named such a protein SAP. The sap gene is highly conserved among GBS strains and homologous genes, such as PulA and SpuA, have been described in other pathogenic streptococci. The SAP protein contains two N-terminal carbohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…SAG_1216), corresponding to residues 41 to 1214, was amplified, cloned, and expressed in bacterial cells as described in Materials and Methods. As previously reported, two expression forms are evident following sodium dodecyl sulfate-polyacrylamide gel electrophoresis, with two bands visible at 98 kDa and 139 kDa, corresponding to a N-terminally truncated form (SAP-L) and a full-length form (SAP-H), respectively (31). SAP-L accounts for 80 to 90% of the total expression and arises due to a second translation start site at Val346 (GTG), a phenomenon also observed for the type I pullulanase from Anaerobranca gottschalkii (6,31).…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…SAG_1216), corresponding to residues 41 to 1214, was amplified, cloned, and expressed in bacterial cells as described in Materials and Methods. As previously reported, two expression forms are evident following sodium dodecyl sulfate-polyacrylamide gel electrophoresis, with two bands visible at 98 kDa and 139 kDa, corresponding to a N-terminally truncated form (SAP-L) and a full-length form (SAP-H), respectively (31). SAP-L accounts for 80 to 90% of the total expression and arises due to a second translation start site at Val346 (GTG), a phenomenon also observed for the type I pullulanase from Anaerobranca gottschalkii (6,31).…”
Section: Resultssupporting
confidence: 74%
“…We have recently reported that incubation of GBS in the presence of sera from animals immunized with SAP impaired the capacity of the bacterium to degrade alpha-glucans in vitro (31). Based on these data and the evidence reported in this paper that recombinant SAP binds to host cells, we propose to use SAP as a potential vaccine component.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations